Effect of fluoride gels with nanosized sodium trimetaphosphate on the in vitro remineralization of caries lesions - Nagata, Mariana Emi [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Báez-Quintero, Liliana Carolina [UNESP]; Danelon, Marcelle [UNESP]; Sampaio, Caio [UNESP]; Monteiro, Douglas Roberto [UNESP]; Wiegand, Annette; Pessan, Juliano Pelim [UNESP] (FapUNIFESP (SciELO), 2023)
Objective: To evaluate the effects of fluoride (F) gels supplemented with micrometric or nano-sized sodium trimetaphosphate (TMPmicro and TMPnano, respectively) on the in vitro remineralization of caries-like lesions. Methodology: Bovine enamel subsurface lesions (n=168) were selected according to their surface hardness (SH) and randomly divided into seven groups (n=24/group): Placebo (without F/TMP), 4,500 ppm F (4500F), 4500F + 2.5% TMPnano (2.5% Nano), 4500F + 5% TMPnano (5% Nano), 4500F + 5% TMPmicro (5% Micro), 9,000 ppm F (9000F), and 12,300 ppm F (Acid gel). The gels were applied in a thin layer for one minute. Half of the blocks were subjected to pH cycling for six days, whereas the remaining specimens were used for loosely-(calcium fluoride; CaF2) and firmly-bound (fluorapatite; FA) fluoride analysis. The percentage of surface hardness recovery (%SHR), area of subsurface lesion (ΔKHN), CaF2, FA, calcium (Ca), and phosphorus (P) on/in enamel were determined. Data (log10-transformed) were subjected to ANOVA and the Student-Newman-Keuls’ test (p<0.05). Results: We observed a dose-response relation between F concentrations in the gels without TMP for %SHR and ΔKHN. The 2.5% Nano and 5% Micro reached similar %SHR when compared with 9000F and Acid gels. For ΔKHN, Placebo and 5% Nano gels had the highest values, and 5% Micro, 2.5% Nano, 9000F, and Acid gels, the lowest. All groups had similar retained CaF2 values, except for Placebo and Acid gel. We verified observed an increase in Ca concentrations in nano-sized TMP groups. Regarding P, TMP groups showed similar formation and retention to 9000F and Acid. Conclusion: Adding 2.5% nano-sized or 5% micrometric TMP to low-fluoride gels lead to enhanced in vitro remineralization of artificial caries lesions.
Keywords: Dental Enamel; Fluorides; Nanoparticles; Nanotechnology; Phosphates